Validity of the Cultivation Agreement Regarding Land Tenure Absentee Caused by Regional Expansion - Muhammad Rifaldi Setiawan; Hera Alvina Satriawan (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This study aims to analyze the legal validity of the Cultivation Agreement issued by the North Lombok Land Office as a form of legal protection for absentee land tenure arising from regional expansion. This research employs a normative legal method using statutory, conceptual, and case approaches, supported by empirical data obtained through interviews. The results indicate that the issuance of the Cultivation Agreement is carried out through administrative mechanisms, including complaint submission, verification, and discretionary decisions by the Head of the Land Office, taking into account social, economic, transportation, geographical factors, as well as regional spatial planning. However, from a juridical perspective, the Cultivation Agreement lacks a strong legal basis and contradicts the prohibition of absentee land ownership as regulated under the Basic Agrarian Law (UUPA) and Government Regulation Number 224 of 1961 in conjunction with Government Regulation Number 41 of 1964. Furthermore, its issuance exceeds administrative authority, as it constitutes discretion within a bound authority framework. Therefore, the Cultivation Agreement cannot be considered a valid form of legal protection.